Quality of work life among librarians in Universiti Teknologi MARA (UiTM) libraries in Malaysia - Abdul Aziz, Rafidah; Mohd. Nadzar, Fuziah; Husaini, Haslinda (2011)
The success of any organization is highly dependent on how it attracts workers, motivates, and retains its workforce. Today's organizations need to be more flexible and understanding, so that they are well prepared to develop their employees and enjoy their commitment. For most employees, going to work can be burdensome and somewhat forced upon them to carry out every day. However, for a few, their careers are the most important thing in their lives compared to others. Quality of work life also includes the level of job satisfaction among employees, salary/remunerations paid by the employer, and whether they are always being motivated either by their colleagues or superior. This can be considered as the contributing factor in reducing stress experienced by employees and allowing them to spend extra time with their family. Stresses happened due to work overload and under load, work shifts or changes need to be improved or sufficiently reduced to ensure emotional stability among employees. An academic library is recognized as an active institution of scholarly literature and holds numerous collections to meet their users' needs. For that reason, it strength has to feature prominently in the range of its resources and a quality workforce. Essentially, for an organization to be able to attract high quality workforce, it needs to provide a better quality of work life. The following elements are relevant to an individual's quality of work life; i.e. the task; physical work environment; and social environment within the organization; administrative system and relationship with peer or colleague. Quality of work life can be defined as "The quality of relationship between employees and the total working environment". The phrase "quality of work life" has also been used to describe working conditions and expectations of most workers in their work life.